Career planning development in system engineering students - Sandoval R.R. (2018)
it is well known that an economy based on knowledge has a strong potential for human capital. In this sense, universities have a key role in student's professional development and performance, as well as to increase the number of professional population in science, technology, engineer, and mathematics. The aim of the present study is to obtain student's individual, structural and external characteristics by considering their context, which represents a condition that shape student's interest, persistence and goals in computing engineering discipline through career development. To accomplish this, we used self-reports based on Social Cognitive Career Theory in a sample of system engineering students (n=270) from three universities in the north of Lima. In addition to this, we evaluate the model through Structural Equation Modeling (SEM) under the partial least squared (PLS-SEM) approach. Results showed different associations and effects in individual and contextual variables among system engineering students.